Halal food supply chain knowledge and purchase intention - Mohd Yusoff, Fara Adura; Raja Yusof, Raja Nerina; Hussin, Siti Rahayu (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This study examines the influence of halal supply chain knowledge on Muslim and non-Muslim consumers’ intention to purchase halal food products. This includes knowledge of halal feed, the halal slaughtering process, halal handling and storage, halal packaging, halal logistics, and halal retail. Convenience sampling was used as the sampling method for the study. Targeted respondents were both Muslim and non-Muslim consumers in Selangor, Kuala Lumpur, and Putrajaya (Klang Valley) in Malaysia. Based on the suggestion from Roscoe (1975), 360 respondents were targeted for this study. Out of 360 questionnaires distributed, 304 (84 percent) were usable and valid for further analysis. This study focused on knowledge supply chains and further identified that knowledge has a direct influence on consumers’ purchase intention for halal food. Knowledge of halal slaughtering, storage, and packaging, in particular, are among the best predictors of consumers’ purchase intention for halal food. Shaari and Arifin (2010) found that knowledge is a key influence in halal purchase intention. However, in terms of the supply chain, knowledge of the process tends to be focused around people in the industry and not general consumers. Hence, this study investigated how far consumers’ knowledge of halal supply chains affects their purchase intention.